Panoplia Multiforme. Scudi allegorici e armature eroiche nei ‘Punica’ di Silio Italico - Cecconi, Niccolò (O T I V M, 2019)
Subject of Silio Italico’s ‘Punica’, the longest epic poem in latin literature, is the second punic war. The poet of the flavian age follows the most important stages of those events, enriching them with episodes of the myth. In this scenario there are a countless number of symbolic objects, including shields and armor. The study, particularly, tries to offer new useful data to understand the articulated role that decorated shields and heroic armor played in the ‘Punica’ and in the imagery of the proto-imperial age.